Pengaruh Pemanfaatan Internet Dan Lingkungan Keluarga Terhadap Keefektifan Pembelajaran Daring Mahasiswa - Tiara Diah Utami; Jonet Ariyanto Nugroho; Khersna Bayu Sangka (Jurnal Pendidikan Nonformal, 2022)
The purpose of the research is to determine the effect of using the internet and the family environment on the effectiveness of online learning, knowing the use of the internet on the effectiveness of online learning, knowing the effect of the family environment on the effectiveness of online learning for students of the Faculty of Teacher Training and Education, Seberang Maret University, class of 2019 in the Kentingan campus area. . The research method is descriptive quantitative. The population is 1436 and the sample is 313 students. Questionnaires are used as a data collection technique. The data analysis technique used is multiple linear regression analysis using the SPPS version 23 program. The results obtained based on this study are: (1) There is a simultaneous significant effect between the use of the internet and the family environment on the effectiveness of learning which can be determined by the value of Fcount>Ftable and sig<0.05, namely 62.612>3,024775 and 0.000 <0.05. (2) There is a positive and significant influence on the use of the internet with the effectiveness of online learning as indicated by the value of tcount> ttable, namely 4.456> 0.967721., and (3) There is a positive and significant influence of the family environment on the effectiveness of online learning, namely by knowing that tcount> ttable ie 7.971>0.967721. Regression equation Y = 13,500 + 0,231X1 + 0,253X2